2022
DOI: 10.3390/en15051741
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Rigorous Consideration of Occupant Behaviours of Residential Households for Effective Electrical Energy Savings: An Overview

Abstract: There are two primary ways to save energy within a building: (1) through improving building engineering structures and adopting efficient appliance ownership, and (2) through changing occupants’ energy-consuming behaviors. Unfortunately the second way suffers from many challenges and limitations. Occupant behavior is, indeed, a complex and multi-disciplinary concept depending on several human factors. Although its importance is recognized by the energy management community, it is often oversimplified and naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Energy conservation in the domestic environment has been largely studied in its multiple facets, as proven by the available reviews and meta-studies [39,[148][149][150]. It emerges that due to the complex nature of the topic, the survey is the most widely used research means [28,56,58,105,106,108,124,138,142,151].…”
Section: Research Methods Gaps and Frontiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy conservation in the domestic environment has been largely studied in its multiple facets, as proven by the available reviews and meta-studies [39,[148][149][150]. It emerges that due to the complex nature of the topic, the survey is the most widely used research means [28,56,58,105,106,108,124,138,142,151].…”
Section: Research Methods Gaps and Frontiersmentioning
confidence: 99%
“…[164]; Fatoki 2022 [165] Need for an integrated approach Gaspari et al, 2021 [28]; Dietz et al, 2013 [166]; Gram-Hanssen 2013 [167]; Savvidou et al, 2020 [168] 4.1. Chance for Savings and Role of Users' Behavior Nowadays, the majority of researchers in the field agree that occupants can strongly affect the energy demand, either acting on the physical features of the building or changing energy use practices [39,40]. Accordingly, energy-saving opportunities emerging from the selected articles can be grouped into two main clusters:…”
mentioning
confidence: 99%
“…A review paper on educating occupants [34] concluded that energy savings of 4-30% are possible. However, as a problem on the part of occupants in general, many studies [35][36][37][38] pointed out that there is a large gap between knowledge and behavior regarding energy saving. If these behaviors could be practiced, energy consumption would be reduced, which is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…People are at the center of energy efficiency efforts, and an understanding of the behavioral sciences can help develop smarter policies" [7]. Bouktif, S. et al [8] have re-viewed the accounting of household behavior in energy conservation.…”
Section: Introduction or Historymentioning
confidence: 99%